Uma plataforma para realizar interações naturais via gestos em ambientes inteligentes - PIMENTA, Igor Gonzalez (2016)
With the development of embedded systems and technologies that use wireless networks, we can see progress in the area of ambient ubiquitous and the interest in the studies of interactions between human beings and electronic devices through natural actions. This new scenario favors the development of ubiquitous computing that is guided by the idea of computing be present to be transparent and available to humans.The evolution of this new phase of computing depends on several aspects, one of the most important the possibility of occurrence of human-computer interactions are more and more natural way, in which the importance of body language is increasing gradually. With contribute to studies in the area of Natural Interactions, this dissertation proposes creating a model of interaction via gestures based on three layers: (i) the Interaction Layer, which will handle the capture of user commands through gestures; (Ii) management layer, which provides a middleware to address the recognition of sensors and actuators in the interaction scenario, besides taking care of the communication between the different components of the model; and (iii) Execution Layer, responsible to associate microcontrollers to electronic devices present in ambient ubiquitous, enabling commands triggered by users from becoming interactions with devices, such as televisions, home theater, lights, curtains, windows, doors , among others. Therefore, a guided platform in model specifications was built, allowing the components used were validated, verifying their performance and evaluating the proposed human-computer interaction (HCI). The main contribution of this paper is to propose a new approach to make life easier for different profiles of persons, including those who have movement restrictions, elderly and children. In addition, the platform provides a low financial cost, enabling people from different social classes can enjoy its benefits.